Rules and Practices of Women’s Inheritance Rights in Islam: Bangladesh Perspective - Mostofa, Md. (International Journal of Islamic Business & Management, 2019)
The study aims to map the status of women right of inheritance in Bangladesh with reference to Islamic injunctions and social practice. For ideal status verses of Holy Quran and traditions of Holy Prophet regarding women right of inheritance are collected. The study concludes that we see most of the people of Bangladesh are reluctant to follow Islamic principles properly with reference to women right of inheritance. Who give women inheritance among of them majority families does not give women inheritance rather provide cash or kind in lieu of their actual shares. Even our society consider dowry as substitute of women right of inheritance. Economic dependency on men, fear of social breakup and conflicts with family and deficiency of proper Islamic knowledge are the reasons for women not to press for their share. Religious scholars should be involved to teach the masses to fulfill their religious obligation of providing actual share of inheritance to women.